1992
DOI: 10.1093/nar/20.9.2287
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the cDNA encoding human DNA methyltransferase

Abstract: We have cloned a series of overlapping cDNA clones encoding a 5194 bp transcript for human DNA methyltransferase (DNA MTase). This sequence potentially codes for a protein of 1495 amino acids with a predicted molecular weight of 169 kDa. The human DNA MTase cDNA has eighty percent homology at the nucleotide level, and the predicted protein has seventy-four percent identity at the amino acid level, to the DNA MTase cDNA cloned from mouse cells. Like the murine DNA MTase, the amino terminal two-thirds of the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
151
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(155 citation statements)
references
References 22 publications
3
151
1
Order By: Relevance
“…[3][4][5][6] However, previous studies have reported that adult mammalian brains, which mainly consist of postmitotic, terminally differentiated neurons and glial cells, express high levels of DNMT1 mRNA and enzyme activity. [7][8][9] In recent in situ and immunohistochemical studies of DNMT1 cellular localization in adult human brains, we provided evidence that DNMT1 is below the limit of detection in cortical pyramidal neurons and in glial cells, but is expressed at unexpectedly high levels in cortical GABAergic interneurons. 10,11 As cortical GABAergic neurons are postmitotic, terminally differentiated cells, the observation that these neurons express relatively high levels of DNMT1 mRNA and protein suggests that in these cells, DNMT1 possesses additional functions beyond the maintenance of DNA methylation at replication foci.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…[3][4][5][6] However, previous studies have reported that adult mammalian brains, which mainly consist of postmitotic, terminally differentiated neurons and glial cells, express high levels of DNMT1 mRNA and enzyme activity. [7][8][9] In recent in situ and immunohistochemical studies of DNMT1 cellular localization in adult human brains, we provided evidence that DNMT1 is below the limit of detection in cortical pyramidal neurons and in glial cells, but is expressed at unexpectedly high levels in cortical GABAergic interneurons. 10,11 As cortical GABAergic neurons are postmitotic, terminally differentiated cells, the observation that these neurons express relatively high levels of DNMT1 mRNA and protein suggests that in these cells, DNMT1 possesses additional functions beyond the maintenance of DNA methylation at replication foci.…”
Section: Introductionmentioning
confidence: 86%
“…The human DNMT1 gene maps to chromosome 19p13.2 7 and linkage studies only weakly implicate markers spanning this chromosome region as susceptibility factors in schizophrenia vulnerability. 57 This, and the fact that in the cortex the overexpression of DNMT1 mRNA is restricted to only certain subsets of GABAergic neurons, makes a DNMT1 DNA sequence mutation as the cause of an alteration of DNMT1 transcription an unlikely possibility.…”
Section: Dnmt1 Mrna Overexpression In Pfc Of Szp Is Restricted To a Smentioning
confidence: 99%
“…For instance, failure to appropriately repress genes has been related to many human diseases, including neurodevelopmental disorders and cancer. 14,15 DNA methylation patterns are established by three independent DNA methyltransferases-DNMT1, DNMT3A, and DNMT3B 16,17 -known to be necessary during neural progenitor cell development. [18][19][20] DNMT1 is mainly implicated in Purpose: Hirschsprung disease (OMIM 142623) is a neurocristopathy attributed to a failure of cell proliferation or migration and/or failure of the enteric precursors along the gut to differentiate during embryonic development.…”
Section: 2mentioning
confidence: 99%
“…DNA methylation in the mammalian genome takes place exclusively at the cytosine bases in CpG dinucleotides. Three known classes of catalytically active DNA (cytosine-5)-methyltransferases (DNMTs), DNMT1, DNMT3a, and DNMT3b, have been cloned and characterized (1)(2)(3). DNMT1 methylates the daughter strands of newly replicated nuclear DNA to preserve the parental methylation pattern.…”
mentioning
confidence: 99%